Skid Row Indians and the Politics of Self - Morinis, E. Alan (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1982)
At the same time as native Indians have been increasing their political lobbying and organizational activity in Canada, the slum neighbourhoods of the inner cities have been witnessing a steady growth in Indian residents. Based on a study of the “Skid Row” Indian community in Vancouver, this paper seeks to link these two apparently disparate phenomena. It is argued that the underlying theme of Indian life on Skid Row is also political. The self-neglect, violence and other disvalued behaviours of Skid Row are seen as the political statements of a group who sees itself as powerless. Acting out the political process of the rejection of society on the stages of their own personal minds and bodies, Indians engage in “the politics of self”.